The Book Of Knowledge In Ṣaḥīḥ Ibn Ḥibbān: From Ḥadīth-source Epistemology To Deontic Modals - Muhammad Fawwaz Bin Muhammad Yusoff; Nur Adlina Binti Zainal Abidin; Mohamad Khalid Bin Bahrudin; Khadher Bin Ahmad (Brill, 2025)
Due to the absence of his opinions and legal theories in the Islamic legal tradition, Ibn Ḥibbān’s legal theory outlined in his introduction to the Ṣaḥīḥ, initially known as al-Taqāsim wa-l-Anwāʿ (the divisions and the categories), has managed to escape the notice of modern scholarship. This article seeks to provide an in-depth overview of the divisions and classifications of Ṣaḥīḥ Ibn Ḥibbān within the framework of hadith study and Islamic legal theory, commonly known as uṣūl al-fiqh. To perform a thorough investigation of this early collection of ḥadīth, we have chosen a Book of Knowledge or Kitāb al-ʿIlm from Ṣaḥīḥ Ibn Ḥibbān. We will demonstrate the epistemic and deontic modals of obligatory, prohibited, formative, permissible, and exclusive aspects by using his al-taqāsim (divisions) and al-anwāʿ (categories) in Kitāb al-ʿIlm. The fundamental principle of al-Taqāsim wa-l-Anwāʿ is that epistemic and deontic modals should align with the Divine command. This structure aims to achieve an ethical state of affairs that is expressed as Sunnah, a term that denotes the practise of the Prophet.